PELATIHAN PEMBUATAN PAKAN IKAN MANDIRI DAN PEMASARAN DIGITAL UNTUK PENINGKATAN DAYA SAING USAHA PERIKANAN AIR TAWAR DI PALANGKA RAYA, KALIMANTAN TENGAH - Muh. Supwatul Hakim; Riandy Putra; Devi Yuliantina; Ersa Aini Safira; Tasya Amalia; Rahmita Sari (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
The fishing industry in Palangka Raya City, Central Kalimantan Province, has great potential for development. However, farmers face problems related to feed availability and prices, as well as limitations in digital marketing. This community service program aims to provide skills to the “Berkat Bersama” Business Group through training in independent fish feed production using local materials with automatic machines and digital marketing training. The activities were carried out in a participatory manner, including preparation and coordination, procurement of materials, assembly of feed printing equipment, module development, dissemination of information on the importance of quality feed and the use of local materials, and training on marketing strategies using digital media. Monitoring and evaluation were conducted through pre-tests, post-tests, and participant testimonials. The pre-test results showed that the majority of participants were in the “Poor Understanding” (75%) and “No Understanding” (12.5%) categories. After the training, there were no more participants in these two categories, while 12.5% of participants reached the “Fair Understanding” category, 25% “Understanding,” and 25% “Very Understanding.” Participant testimonials reinforce that this program is useful as a means to increase independence in feed supply, expand the marketing network for fishery products, and strengthen the competitiveness and sustainability of freshwater fish farming businesses in Palangka Raya.